(untitled) (Al Basirah, 2020)
The ethnic and Islamophobic trends were present in the western discourses since long but they increased in number and intensity in the post 9/11 scenario. The co-existence of Islamophobic trends in the European discourse did not only influence political and financial structures but also the social and cultural edifices. The paper attempts to analyze the representation of Muslims and Islam in the British media in the light of the available literature. The paper concluded that the British Muslims were framed as alien “Others” by the British media. The portrayal of “others” was further linked to the racist notions of Islamophobia. The dominant themes employed by the British press for the portrayal of Muslims included „deviant‟, “immigrants”, “dangerous”, “problematic, and “oppressive”. The western media‟s tendency of frequently engaging their own commentators for commenting on matters related to Islam and Muslims was considered as a main reason for biased representation of Islam and Muslims in the Western media. Resultantly it is always “Us” which is representing “Them” instead of “They” representing “Themselves”. Thus the western media tends to portray Islam and West as opposites to each other.